Physicochemical and nutritional quality of smoke catfish (Clarias gariepinus) with coconut shell liquid smoke during frozen storage - Setyastuti, Aryanti Indah; Prasetyo, Dwi Yanuar Budi; Kresnasari, Dewi; Kurniawati, Any; Sarmin, Sarmin; AGS, Dwi Apriliani (Acta Aquatica: Aquatic Sciences Journal, 2021)
This research was aims to determine the effect of coconut shell liquid smoke application on the smoking process on the physicochemical quality of smoked catfish stored at freezing temperature for 14 days. The test parameters used were proximate analysis (protein, fat, and water content), salt-soluble protein, pH, texture (adhesion, springness, cohesiveness, hardness). Analysis of the data in this experiment using a completely randomized design with different storage time treatments (0 days; 7 days; and 14 days) at freezing temperatures. The results of the analysis of variance showed that the application of coconut shell liquid smoke to smoked catfish gave a significant difference (P <0.05) to the physicochemical quality including proximate, salt-soluble protein, pH, and texture. During storage, there was a decrease in the proximate value and salt soluble protein of smoked catfish, while the pH value increased. Meanwhile, texture, adhesion, springiness, and cohesiveness values decreased along with the decreasing proximate value of smoked catfish, and the hardness value showed an increase during storage resulting in a harder texture of fish meat due to protein denaturation.Keywords: Coconut shell liquid smoke; Frozen storage; Physicochemical quality; Smoked catfish nutritional